Design of temporary, conditional, general and highly influential buildings for tropical cyclones and severe local storms. Issue 16 (December 2022) - Tamura, Yukio; Yang, Qingshan; Wang, Yu
This paper first discusses the causes of damage to buildings and structures due to various types of winds including daily winds and some extremely strong winds. Regarding devastating wind-induced disasters due to tropical cyclones (TC), the importance of combined effects of wind and water hazards is emphasized. It also points out human errors hidden in damage scenarios, especially for large buildings. The importance of cladding/component design, the significance of debris impacts, and the effects of sudden changes in internal pressures are also emphasized. The design principles for buildings and structures are also examined, and the crucial differences among building performances against TCs and severe local storms such as tornadoes and downbursts are discussed. Design load levels for temporary buildings including scaffoldings and construction offices and for conditional buildings and structures including cranes, movable roofs and so on are also discussed. Next, design issues of tornado effects on highly important and highly influential buildings such as nuclear power plants are discussed. Finally, to cope with the future increasing trend of wind-related disasters, the importance of decarbonization and full-scale storm simulators are emphasized.